“A Vivência da Reprovação Escolar por Estudante de uma Escola Pública de Ensino Médio: um Estudo à Luz da Teoria Biológica do Desenvolvimento Humano”. - Pacheco, Marcos da Silva (2021)
School failure, although considered at first glance as an event that is often negative and unwanted during the training process, can function, according to teachers, parents and even students as a mechanism of selection, coercion and justice. Such a process retains those students who were unable to achieve the necessary knowledge and minimum objectives recommended by the curriculum. The effects of failure can go far beyond the delay of a year in the student's life, and can result in changing plans for the future, conflicts with parents, loss of job opportunities, prejudiced actions, loss of friendship, among others. On the other hand, it is argued that failure can be seen as a second chance to learn content or even for students to mature and acquire new behaviors. In this study we used the Bioecological Theory of Human Development (TBDH), a contextualist theory that is anchored in a model called PPCT, which are the initials of the elements: Proximal Process, Person, Context and Time, pillars of development. We studied the experience of school failure by students from a public high school using the TBDH. A longitudinal study was carried out with three collection times, where information about the history of failures, their causes, opinions about this process and especially about their experience in the year of school failure was collected. In the first moment, before failing, 306 students answered questionnaires on this topic. In the second and third moments, 10 approved and failed students were interviewed, as well as 7 of their teachers in order to study the experience of failure within the school Microsystem. The interviews were transcribed and analyzed using Content Analysis. As a result, we observed that teachers, even without understanding their role, did not give up reprobation as a mechanism of justice and maturation for students who, in turn, took responsibility for it. Passed and failed students negatively evaluated the physical structure of the School Microsystem, but recognized the quality of teaching compared to that experienced in previous schools. Students who failed had a more negative view of teachers and content when compared to those who passed. Failure produced parental reactions such as fights, punishments and disappointment, indicating the establishment of Inverse Proximal Processes in these relationships. Teachers complained that parents did not care or spend time on their children's education, thus attributing an imbalance in this Mesosystem that would harm learning. Passed students had the idea that failure happened because the students did not take the school seriously or put in the effort although they were able to learn if they wanted to, attributing only to Pessoa's characteristics instead of considering other elements of human development. They believed that failure had as its main damage the delay in life plans. The greatest impacts reported by students due to failure were delay and greater difficulty in carrying out life projects. Students still had plans to enter Higher Education, pursue a military career or immediately enter the job market. Approved students also showed interest in joining the university, however, their choices were less ambitious as they sought less competitive courses. Students who passed and failed showed great strength of proximity in their psychosocial support networks.